Current Trends in the Study of Object-Oriented Programming in Higher Education - Tatyana Gainutdinova; Marina Denisova; Olga Shirokova (ARPHA proceedings, 2019)
The article examines the current methodological and technological problems of software development, based on an object-oriented approach in the field of programming. The relevance of the topic is determined by the general need to develop a methodology for teaching object-oriented programming based on object-oriented design. In this paper the problems of teaching object-oriented programming to students studying at the Faculty of Mathematics majoring in teacher education are formulated. The methodology for development of object-oriented projects related to the implementation of mathematical abstractions and structure classes is proposed. The object-oriented programming enables one to take advantage of the object-oriented approach not only at the design stage, but also at the stage of their implementation, testing and maintenance. The creation of object-oriented modeling projects for mathematical systems and structures facilitates the development of skills for problem formulation and highlighting abstractions and objects of a given subject area and the relations between them.